Vanek’s tumor causing ileoileal intussusception in a middle-aged man - Syamim Johan; Pei Pei Lee; Nornazirah Azizan; Firdaus Hayati; Andee Dzulkarnaen Zakaria (Oxford University Press, 2020)
Intestinal obstruction is a common surgical emergency requiring urgent intervention. Small bowel obstruction secondary to intussusception is rarely encountered especially when inf lammatory fibroid polyp (IFP) is the lead point. A 41-year-old gentleman with intestinal intussusception secondary to IFP presented to us with a classic symptom of intestinal obstruction. Computed tomography revealed a target or sausage-shaped soft tissue mass with a layering effect, which was confirmed by intraoperative findings. Histopathology was consistent with IFP and supported by immunoreactivity of CD34 and negative immunostaining for CD117. He recovered without any surgical complication or recurrence. Even intussusception can be managed via non-surgical technique in children; surgery is the mainstay of treatment in adults.